Dysregulation of adaptive immune responses in complement C3‐deficient patients. Issue 3 (19th January 2015) - Pekkarinen, Pirkka T.; Heikkilä, Nelli; Kisand, Kai; Peterson, Pärt; Botto, Marina; Daha, Mohamed R.; Drouet, Christian; Isaac, Lourdes; Helminen, Merja; Haahtela, Tari; Meri, Seppo; Jarva, Hanna; et al.
<x xml:space="preserve">Abstract</x> In addition to its effector functions, complement is an important regulator of adaptive immune responses. Murine studies suggest that complement modulates helper T‐cell differentiation, and Th1 responses in particular are impaired in the absence of functional complement. Here, we have studied humoral responses to toxoid vaccines in eight patients with C3 deficiency, representing more than 25% of all the known patients worldwide. Serum cytokine levels were also studied. The patients developed normal Ig responses to tetanus and diphtheria toxoids, but IgE levels were low. The pattern of antigen‐specific IgG subclasses was abnormal, with increased Th1‐related IgG3 responses, low IgG2, and almost completely undetectable IgG4. The patients also had increased amounts of Th1‐related cytokines IL‐12p70 and IL‐21, and these showed a positive correlation with IgG3 levels. Our results confirm that complement modulates Th differentiation, but reveal a more nuanced outcome than previously reported. Since IgG4 has been linked to tolerogenic responses, the data also suggest that in the absence of functional complement at least some aspects of systemic tolerance are impaired.